Comparison of Ketamine and Propofol-Based Regimens for Deep Sedation in Children Undergoing Esophagogastroduodenoscopy - Akingbola, Olugbenga; Srivastav, Sudesh K.; Nguyen, Michelle; Singh, Dinesh; Frieberg, Edwin M.; Thibodeaux, Amy (Journal of Pediatric Intensive Care, 2020)
We retrospectively reviewed the charts of 180 children sedated for esophagogastroduodenoscopy (EGD) with ketamine or propofol-based regimens at our institution. Pre-EGD diagnoses and American Society of Anesthesiology physical status were similar in all subjects. Onset of action and recovery time for both regimens were not statistically significant (p > 0.05). Mean onset of sedation for all patients was 3.85 ± 3.04 minutes, mean Aldrete score was 6.31 ± 0.61, and mean recovery time was 51.85 ± 31.78 minutes (p > 0.05). Sedation-related adverse events observed include apnea, hypoxemia, bradycardia, hypotension, laryngospasm, skin rash, and wheezing. Deep sedation for pediatric EGD is safe if patients are carefully screened and properly monitored.
Keywords: pediatric EGD; artificial airway; procedural sedation